The stars of the city (Journal of Parents and Teachers, 2014)
Through a store told by Fermin, he and his classmate Airam tell us what the school where they study did to make all kids see the beauty of the Milky Way and the stars, as most of the times we don’t realise that it is so bright at night that kids can’t see the stars, but they still have to study them at school. This is an example of an educational project to work with the basic competencies.
Keywords: didactics; astronomy; light pollution; planetarium